MENINGKATKAN EFEKTIVITAS FINANCIAL FLOW PERUSAHAAN DISTRIBUTOR CONSUMER GOODS MELALUI LAYANAN SUPPLY CHAIN FINANCING BANK DANAMON - , Gunawan Muhamad, Prof. Dr. Sukmawati Sukamulja, MM. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
As one of the links in the supply chain management, distribution companies is required to perform an optimal role in the product stream from the principal to the customer or the next supply chain. In the concept of industry value chain, the distributor is the "bridge" to be traversed by the product or service to deliver the product/service is up to the customer. Based on the characteristics of the business, working capital management and financial management at the company's distribution becomes very important to maintain and improve the effectiveness and efficiency of business. To facilitate this need, Bank Danamon launched a program called supply chain financing. The program is a package of banking services that are integrated to support companies engaged in a supply chain system. Through its supply chain financing, Bank Danamon offers several services and facilities that can be utilized by companies to support their business. This study aims to gain an overview of Bank Danamonâs Supply Chain Financing program model for consumer goods distributors and to understand the business and financial characteristics of the distribution flows. They also analyzed the impact of supply chain financing program for the improvement of financial flow distributor. The method used is descriptive analysis. Grand theory that is used are working capital management and cash flow management. The results showed that the supply chain financing program Danamon Bank offers a package of services such as financing working capital and cash management services. The analysis also showed that the characteristics of the distributor company's business is highly dependent on the financial flow. Supply chain financing program of Bank Danamon have an impact on the financial optimization of the lower cash flow conversion cycle. Decrease in cash conversion cycle days occur through an increase in working capital (DWC) and days payable outstanding (DPO) and the decrease in days sales outstanding (DSO) and days of inventory (DOI). Supply chain financing programs directly impact the increase in days working capital (DWC) and days payable outstanding (DPO). And indirectly impact on the reduction in day sales outstanding (DSO) and days of inventory (DOI).